Ursula Schulz-Dornburg - Sulla strada - Arrigoni, Fabrizio (Firenze Architettura, 2017)
Ursula Schulz-Dornburg’s visual mosaic, in surveying and archiving a little-known heritage of artifacts captures the essence of architecture through its founding values of protection, shelter and refuge. Unexpected buildings whose inventiveness and morpho-typologic richness constitute the vulnerated scene where farewells and returns occur, giving proof of a tenacious resistance to the forgetfulness of men and to the insults of the seasons.